PENGARUH BIAYA PENDIDIKAN DAN FASILITAS PENDIDIKAN TERHADAP HASIL BELAJAR BACA TULIS AL-QUR’AN PESERTA DIDIK TPQ WALISONGO SAWOHAN - Rida Ayu Yuliana (LPPM Universitas Bina Bangsa, 2023)
There are several problems in this study, namely (1) whether the results of learning to read and write the Qur'an of students are influenced by the cost of education, and (2) whether the learning outcomes of students are influenced by educational institutions, and 3) whether there is an influence of the costs of education and institutions education on student learning outcomes to read and write the Qur'an? The subjects of this study were all students of TPQ Walisongo Sawohan, with a total of 219 students. Because this example uses the Slovin table, it gets 142 samples. Data collection techniques using documentation, observation, and survey methods. Documents to confirm student learning outcomes, observations to identify school facilities, and questionnaires to determine the impact of educational and institutional costs on learning outcomes. The results show that (1) the cost of education has an effect on the learning outcomes of TPQ Walisongo Sawohan students in the Al-Qur'an Reading and Writing subject. From the calculation results obtained Fcount > Ftable or 75.97 > 3.92, (2) From the results of the calculation Fcount > Ftable or 59.09 > 3.92 it can be seen that educational institutions have a great influence on learning outcomes. (3) The cost of education and educational institutions is the result of learning based on the results of the calculation of F arithmetic > F table or 49,174 > 3.92